A Case of Mediastinitis due to Perforation of the Cervical Esophagus Associated with Dermatomyositis - Ishida, Naoko; Hirai, Atushi; Ninomiya, Go; Tobinaga, Junichi; Tanaka, Nobutake; Ishigure, Kiyoshi; Kuroda, Hirohumi; Ito, Yoichi; Kato, Koichi; Hayashi, Naomi (The Japanese Journal of Gastroenterological Surgery, 2011)
We report a case of descending mediastinitis due to perforation of the esophagus associated with dermatomyositis. In July 2008, the patient, a 55-year-old woman, complained of the rash on her face. Dermatomyositis was diagnosed and steroids were prescribed. In September, she suffered neck pain and fever. We diagnosed mediastinitis due to perforation of the cervical esophagus, based on esophagograms and cervicothorasic computed tomography (CT). We operated the cervical and mediastinal drainage through anterior neck. Seven days later, CT revealed an effusion in the right thoracic cavity and posterior mediastinum. Therefore we performed additional thoracic and mediastinal drainage through a right thoracotomy. The mediastinitis improved after that operation. However, it also took time to heal the cutaneo- esophageal fistula. She was released from hospital with tube feeding 162 days after her first surgery, and we reoperated after her closed fistula was found on the 205th day. There are some reports that dermatomyositis has caused the complication of a digestive tract ulcer, but they rarely cause perforation. In this case, the patient was saved by cervicothorasic drainage for the mediastinitis caused by the fistula during the treatment of her dermatomyositis.